Building effective business relationships in China - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2012)
China’s ways of doing business are becoming more Westernized. But non-Chinese executives still must work hard at building trust in relationships with their Chinese business partners.